(untitled) (Journal on Excellence in College Teaching, 2024)
This article illustrates how 10 faculty members partnered as a professional learning community (PLC) to evaluate and improve their reflective practices focused on teaching. Their overarching goal was to enhance their effectiveness as teacher educators by identifying and using new methods in their courses while also providing professional development to their departmental peers drawn directly from what they were learning. As is the nature of PLCs, members set individual and collective goals. They summarize the multi-layered nature of this dynamic phenomenon, articulate the structured methodological process used, and discuss the findings and implications of the PLC’s work towards meaningful teaching and learning.